Comparative climate change impacts of different strawberry cultivation systems in Southeastern Europe: A study across open-field and protected cultivation systems towards sustainable production models - Frakolaki, Georgia; Parcharidou, Maria; Boukouvalas, Christos; Papadaki, Sofia; Panagiotou, Nikolaos; Valanides, Nicolas; Kokkini, Anna; Georgiadou, Egli C.; Milivojević, Jasminka; Tsormpatsidis, Evangelos; Raffaelli, Davide; Mezzetti, Bruno; et al. (My University, 2025)
The current study evaluated the climate change impacts of three different strawberry cultivation systems (open-field, protected soil-based, and protected soilless cultivation) across four Southeastern European countries: Serbia, Greece, Cyprus and Italy. To this aim, a Life Cycle Assessment (LCA) was employed in accordance with ISO 14040/14044 standards and ReCiPe2016 (H) was chosen as the impact assessment methodology. The objectives of the study were twofold: first, to develop a life cycle inventory (LCI) encompassing all flows and processes related to strawberry production, and second, to identify the practices and processes contributing the most significant environmental burden. The scope of the study was focused on crop production; thus, the boundaries of the system were set as cradle-to-farmgate and the assessment covered all in-field processes: the land preparation, the planting, the fertilization and pesticides' use, the irrigation and the harvest. Post-harvest management practices were assumed to be similar across the different systems and thus fall outside the scope of this study. Results indicated significant differences across the countries examined and the cultivation systems tested. Cyprus exhibited the highest global warming potential, primarily due to excessive fertilizer use in soilless cultivation, while Serbia showed the lowest impact, reflecting more sustainable-sourced agricultural practices. Among the different countries and cultivation systems examined, the open field cultivation in Cyprus and protected soilless cultivation in Serbia exhibited the highest water consumption, driven by climate conditions and plant density differences. The trade-offs reported herein illustrate that no cultivation system performs best across all impact categories; instead, each system's advantages come at a cost in another environmental dimension. Our findings underscore the importance of adopting region-specific strategies to optimize sustainability in capital-intensive strawberry production systems.
Keywords: Strawberry cultivation; Sustainability; Life cycle assessment; Greece; Cyprus; Serbia; Italy